2006
DOI: 10.1111/j.1540-8167.2006.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Video‐Assisted Thoracoscopy to Treat Atrial Tachycardia Arising from Left Atrial Appendage

Abstract: A 17-year-old male with tachycardia-induced cardiomyopathy presented with persistent, drug-resistant atrial tachycardia (AT). An electrophysiological study suggested focal abnormal automaticity, and localized the AT origin to the left atrial appendage. Radiofrequency catheter ablation at the site of the earliest endocardial activation during AT failed. A minimally invasive, video-assisted thoracoscopic (VAT) atrial appendectomy terminated the AT and restored left ventricular contractility. The patient remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…410,20 In general, these have been de novo ATs unrelated to AF/ablation and have been mapped to a single site, as one would expect with a focal AT. However, these studies did not perform high-density mapping of the arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…410,20 In general, these have been de novo ATs unrelated to AF/ablation and have been mapped to a single site, as one would expect with a focal AT. However, these studies did not perform high-density mapping of the arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…13 Besides sporadic cases, systematically conducted studies have reported electrocardiographic and electrophysiologic characteristics of focal atrial arrhythmias arising from the LAA. 410 However, little is known about the mechanism and characteristics of organized atrial arrhythmia, atrial tachycardia (AT), arising from LAA in association with the ablation of persistent AF (PsAF). 11 We present the incidence, electrophysiologic characteristics, and outcomes of LAA AT arising in the context of PsAF ablation in a consecutive series of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although percutaneous epicardial approach for ablation of accessory pathways involving the right atrial appendage has been described, 5 to our knowledge this is the first report of successful ablation of ectopic atrial tachycardia from the left atrial appendage using this approach. The unique problems associated with management of tachycardias arising from the left atrial appendage have required surgical intervention 7 and excision of the appendage in several reported cases 8,9 . Although some of the difficulties in satisfactory delivery of RF energy within the low‐flow appendage have been obviated by the use of an irrigated‐tip ablation catheter, 4 these cases highlight the potentially important role of minimally invasive percutaneous epicardial mapping and ablation in the management of left atrial appendage arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with traditional open thoracotomy, videoassisted thoracoscopic surgery is less invasive and has the advantages of fewer complications, lesser post-operative pain, and a shorter hospitalisation period. 8 To our knowledge, the patient in our case is the youngest reported patient to undergo successful minimally invasive thoracoscopic atrial appendectomy through the joint efforts of a paediatric intensivist, electrophysiologist, and cardiac surgeon.…”
mentioning
confidence: 76%